WOMEN PARTICIPATION IN LOCAL BODIES OF KERALA - SURESH O (ECOSENTIMENTS JOURNAL, 2013)
Women in Kerala occupy a pride of place among their counter parts in the rest of the country. However, compared to the status of men in states, they remain much lower in the ladder. The situation is not different in the case of changed political scenario at the level of governance. Around 50 per cent of the seats in the LSGS of Kerala have been allotted to women through legislation. In this context, it is pertinent to study their participation in local bodies.